Domain analysis of language choice and English language use among lecturers in a Malaysian public university - Tam, Lee Mei (2014)
It is a norm for people from all walks of life to choose and use which language(s) to communicate when they come into contact with each other. In a multilingual and multicultural country such as Malaysia, almost everyone speaks at least two or more languages. Thus, the Malaysian multilingual situation resulted in speakers having to make decisions about which languages are to be used for different purposes in different domains. In order to explain the phenomenon of language choice, Fishman domain analysis (1964) was adapted into this research. According to Fishman’s domain analysis, language choice and use may depend on the speaker’s experiences situated in different settings, different language repertoires that are available to the speaker, different interlocutors and different topics. Such situations inevitably cause more barriers and difficulties to those professionals who work in education domain. Therefore, it is this research’s purpose to explore the language choice and use of a Malaysian public university’s lecturers in the domains of family, friendship, education and transaction. Besides, this research wants to examine whether any significant differences between ethnicity and field of study with the language choice and use of Malay, Chinese and Indian respondents in the domains of family, friendship, education and transaction. Another area of focus is to investigate the significant differences between English language choice and use of the respondents in relation to their ethnicity and field of study. 200 survey questionnaires were distributed to ten faculties of a Malaysian public university to examine the details of the lecturers’ language choice and use. The findings of this research suggested that the language choice and use of Malay respondents generally preferred to choose and use Malay language across all domains identified except when they are in formal education domain. As for Chinese respondents, they preferred to choose and use the English language in all of the listed domains apart from the family domain. The Indian respondents also chose and used more English language than their own ethnic language in all of the domains. Besides, all of the respondents claimed that they chose and used more than one language in all domains. The ANOVA results showed that significant differences were found in the three ethnic groups in their language choice and use of the English language in the four domains (family, friendship, education and transaction). As for the independent sample t-test, significant differences were discovered between Sciences and Social Sciences lecturers in their language choice and use in domains of friendship, education, and transaction; but not in the family domain. This means in the family domain, the use of English language between Sciences and Social Sciences lecturers did not differ significantly. This research found that the respondents chose and used their ethnic language more frequently in informal domains while English language was preferred more in formal domains. The findings in this research have provided a clear spectrum of the language choice and use of the Malay, Chinese and Indian respondents in the education domain complemented by family, friendship and transaction domains. In addition, this research suggested that the language and educational policy makers have been largely successful in raising the role and status of the English language as the medium of instruction in tertiary education while maintaining the Malay language as having an important role in the communicative acts characterizing the lecturers’ language choice and use.